Factors Associated With HIV Preventive Behavior Among Adults in Majang Zone of Gambella Region, Southwest Ethiopia - Yosef, Tewodros; Wondimu, Wondimagegn; Nigussie, Tadesse; Asefa, Adane; Qanche, Qaro; Mekonnen, Besufekad; Mesafint, Gebremeskel; Shifera, Nigusie; Amsalu, Hailemariam; Bekele, Bayu Begashaw (Frontiers in Medicine, 2022)
Background: HIV-positive people can spread the virus through unprotected sex; however, HIV can be avoided if populations are educated about the risks. In underdeveloped nations, evidence suggests that the ABC method for HIV prevention is quite effective. As a result, the goal of this study was to determine the magnitude of HIV prevention behavior among adults in the Majang zone of southwest Ethiopia, as well as the factors that influence it. Methods: A community-based cross-sectional study was carried out from March 1st to May 31st, 2019. The data were collected through a face-to-face interview using a modified validated questionnaire among systematically selected study participants. The collected data were coded and entered using Epidata manager version 4.0.2.101 and analyzed using SPSS version 21. A logistic regression analysis was computed to determine the association using crude and adjusted odds ratios at 95% confidence intervals. The level of significance was declared at a p-value less than 0.05. Results: Of the 772 adults interviewed, the proportion of adults who had good HIV preventive behavior was 51.8%, 95% CI (48.3% - 55.3%). Two hundred forty (31.9%) were used abstinence as a type of HIV preventive behavior followed by being faithful (16.1%) and consistent condom use (7.3%). The study also found that respondents with the age group ≥ 27 years old (AOR=1.56, 95% CI [1.3-3.12]), marital status (being married (AOR=6.30, 95% CI [4.48-11.4]), and divorced/widowed (AOR=5.50, 95% CI [2.60-12.4])) and having good knowledge of HIV prevention methods (AOR=2.18, 95% CI [1.71-4.00]) were the factors associated with good HIV preventive behavior. Conclusion and recommendation: In the study area, overall HIV prevention behavior was average. The characteristics linked with successful HIV prevention behavior among adults in the Majang community included increasing age, being married or divorced/widowed, and having a solid understanding of HIV prevention approaches. As a result, policy-level and multi-sectorial intervention approaches from all stakeholders are necessary to develop short- and long-term strategies to address the problem and improve the community's quality of life.